Durable High Surface Area Electrodes for Rechargeable Zinc Air Batteries - Ahmed, Raihan (University of Waterloo, 2015)
People have shown significant interest in metal air batteries throughout history due to their high energy storage capacities, safety, and low cost. These batteries do not require oxygen, one of their constituent fuels, to be stored inside the cell leading to high volumetric capacities. This is achievable due to the utilization of a unique gas diffusion electrode system that has a complex three phase interface regime. One of the safest and cheapest from the metal air family is the zinc air battery, zinc being one of the most abundant metals on earth. However, researchers have come across various challenges when dealing with these batteries and some of them include sluggish reaction rates, slow gas diffusion rates, and cell material degradation leading to poor power densities and charge-discharge cyclability. This work will address some of these issues via electrode and cell design optimization utilizing some of the proprietary technologies developed in the Applied Nanomaterials and Clean Energy Laboratory. In this work, it has been demonstrated that highly conductive and porous zinc electrodes can be developed that eliminate some of the detrimental dendrite formations usual in conventional zinc based batteries. These electrodes have been made by the use of nanomaterial templates and micellar voids as well as controlled temperature treatments to make strong porous structures making them ideal for use in commercial zinc air batteries. Novel gas diffusion electrodes have also been developed which have very slow rates of passivation in alkaline electrolyte compared to conventional carbon gas diffusion electrodes. These novel gas diffusion electrodes are made using a modified roll pressing method which has been optimized to account for low cost large scale production and porosity ideal for high gas diffusion rates without compromising electrode hydrophobicity and clogging by electrolyte. Cell designs have also been investigated and proposed, ideal for housing the proprietary anodes and cathodes that are leak proof, compact, and recyclable. Each cell benefits from ample cathode area exposure to oxygen and a stack design that makes sure there is sufficient flow of air to the cells to maximize power density.
Keywords: Raihan Ahmed; Zinc Air; Zinc Anode; Bifunctional Cathode; Three Electrode Flow Cell; Chemical Engineering (Nanotechnology)